(untitled) (Philological Studies, 2019)
In the written practice of the Macedonian standard language, very often, a great deal of incompatibility and inconsistency could be noticed regarding the correct use of the rules for writing the correct forms of sounds and words. In this sense, the terms from the area of education are especially important, which could often be found in the written practice of those people who are connected with the area of education in any way, and who, cause dilemmas in the manner in which certain words should be written regarding capital and small letter. Thus, in this paper, certain differences in the written practice of terms which are part of the area of education (with capital or small letter) are shown, and at the same time, it is indicated that the imprecision and the lack of more detailed explanation in these rules in the Orthography result in different interpretations and different realization of the written practice of the language. Consequently, this imposes the necessity of more precise rules regarding this part of the Оrthography of the Macedonian standard language.